IMPLEMENTATION USING SOCIAL MEDIA OPTIMIZATION (SMO) FOR INTERNET MARKETING ON RUMAHDANPROPERTI.COM - david chandra; Hoga Saragih (Jurnal Sistem Informasi, 2011)
Lately, social media like Facebook become one of the methods to do marketing of products and online services. Social Media Optimization (SMO) is a marketing method that is now being developed by many companies in the field of internet marketing. The purpose of this study is the implementation using social media optimization (SMO) on the rumahdanproperti.com website. Rumahdanproperti.com is the website which is the largest property advertising portal in Indonesia which focuses on online business. The research will implement the SMO method using Facebook as a means of product introductions and analyze the use of existing Facebook features in response to rumahdanproperti.com ads. The research method used quantitative analysis and software analysis to measure advertising response to the features used on rumahdanproperti.com facebook. In conducting the quantitative analysis, researcher used questionnaires to obtain data from respondents who are members of this rumahdanproperti.com Facebook. The result of this implementation of the SMO is expected to support companies in introducing their brands to the public. The conclusion of this research, feed and discussion feature on Facebook have an influence on response of rumahdanproperti.com ads. Akhir-akhir ini, media sosial seperti Facebook menjadi salah satu metode untuk melakukan pemasaran produk dan layanan online. Social Media Optimization (SMO) adalah sebuah metode pemasaran yang kini banyak dikembangkan oleh banyak perusahaan di bidang internet marketing. Tujuan dari penelitian ini adalah implementasi menggunakan SMO pada website rumahdanproperti.com. Rumahdanproperti.com adalah website yang menjadi portal iklan properti terbesar di Indonesia yang berfokus pada bisnis online. Penelitian ini akan menerapkan metode SMO menggunakan Facebook sebagai sarana pengenalan produk dan menganalisis penggunaan fitur Facebook yang ada dalam menanggapi iklan rumahdanproperti.com. Metode penelitian menggunakan analisis kuantitatif dan analisis perangkat lunak untuk mengukur respons iklan untuk fitur yang digunakan pada facebook rumahdanproperti.com. Dalam melakukan analisis kuantitatif, peneliti menggunakan kuesioner untuk mendapatkan data dari responden yang menjadi anggota facebook rumahdanproperti.com ini. Hasil dari pelaksanaan SMO diharapkan untuk mendukung perusahaan dalam memperkenalkan merek mereka kepada publik. Kesimpulan dari penelitian ini fitur, pakan dan diskusi di Facebook memiliki pengaruh pada respon iklan rumahdanproperti.com.